Comparison of lower limb muscle architecture and geometry in distance runners with rearfoot and forefoot strike pattern - Gonzales, J. M.; Galpin, A. J.; Montgomery, M. M.; Pamukoff, D. N. (Journal of Sports Sciences, 2019)
We examined the association between footfall pattern and characteristics of lower limb muscle function and compared lower limb muscle function between forefoot and rearfoot runners. Fifteen rearfoot and 16 forefoot runners were evaluated using ultrasonography of the gastrocnemii and tibialis anterior while strike index and heel strike angle quantified footfall pattern. Higher strike index was associated with lower medial gastrocnemius echo intensity (p = 0.05), lower lateral gastrocnemius echo intensity (p = 0.04), smaller tibialis anterior pennation angle (p = 0.05), and longer lateral gastrocnemius fascicle length (p = 0.04). Larger heel strike angle was associated with smaller medial gastrocnemius cross-sectional area (p = 0.04), shorter lateral gastrocnemius fascicle length (p < 0.01), and lower plantar flexion moment (p < 0.01). Larger plantar flexion moment was associated with lesser medial gastrocnemius echo intensity (p = 0.04), lesser lateral gastrocnemius echo intensity (p = 0.03), and greater lateral gastrocnemius fascicle length (p = 0.02). A smaller plantar flexion moment, larger heel strike angle, lower tibialis anterior echo intensity, larger tibialis anterior pennation angle, and smaller lateral gastrocnemius pennation angle were observed in rearfoot compared to forefoot runners (p < 0.05). Lower limb muscle architecture is associated with footfall pattern and ankle mechanics during running.